Genetic polymorphisms analysis of drug-metabolizing enzyme CYP2C9 in the Uyghur population. (2nd August 2016) - Jin, Tianbo; Xun, Xiaojie; Du, Shuli; Geng, Tingting; Wang, Hong; Feng, Tian; Chen, Chen; Yuan, Dongya; Kang, Longli
Abstract: Genetic variations in cytochrome P450 2C9 are known to contribute to interindividual and interethnic variability in response to clinical drugs, but little is known about the genetic variation of CYP2C9 in the Uyghur population. We directly sequenced the whole CYP2C9 gene in 96 unrelated, healthy Uyghur from Xinjiang Uygur Autonomous Region of China and screened for genetic variants in the promoter, exons, introns and 3′-UTR. Thirty five previously reported alleles and six genotypes were detected in this study. The allele frequencies of CYP2C9 *1, *2, *11, *12, *29 and *33 were 89.58, 7.81, 0.52, 0.52, 1.04 and 0.52%, respectively. We detected one non-synonymous novel variant at position 329 from Arg to Cys and this mutation is predicted to be intolerant by SIFT. Our results provide basic information about CYP2C9 alleles in Uyghur, which may help to optimize pharmacotherapy effectiveness by providing personalized medicine to this ethnic group.